Unusual Single-Ion Non-Fermi-Liquid Behavior in Ce1-xLaxNi9Ge4 - Killer, U.; Scheidt, E.-W.; Eickerling, G.; Michor, H.; Sereni, J.; Pruschke, T.; Kehrein, S.; Sereni, Julián (American Physical Society, 2004)
Fil: Sereni, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina